INFLUENCE OF FINTECH, LIFESTYLE HEDONISM, AND PEERS ON THE FINANCIAL BEHAVIOR OF STUDENTS - Ardiansyah, Mohammad Fredy; Marina, Anna; Sa’diyah, Halimatus (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis, 2025)
Financial management behavior plays an essential role in students' lives, particularly in the face of evolving technology and modern lifestyle dynamics. This research investigates how Financial Technology, a hedonistic lifestyle, and peer influence affect the financial management behavior of accounting students at universities in Surabaya. Employing a quantitative approach with an explanatory research design, the study involved a sample of 370 accounting students chosen through purposive sampling. The data were analyzed using multiple linear regression with SPSS version 26. The findings reveal that Financial Technology exerts a positive and significant impact on students’ financial management behavior. In contrast, a hedonistic lifestyle demonstrates a significant negative impact, while peer groups contribute a positive and significant effect. Collectively, these three variables significantly influence the financial management behavior of accounting students.